Balanced and positively worded personality short-forms: Mini-IPIP validity and cross-cultural invariance - Agustín Martínez-Molina; Víctor B. Arias (PeerJ, 2018)
Background The Mini-IPIP scales (Donellan et al., 2006) are possibly one of the most commonly used short inventories for measuring the Big Five Factors of personality. In this study, we aimed to investigate the psychometric properties of two Mini-IPIP Spanish short forms, one balanced and one positively wording (PW). Method Two samples, one from native Spanish speakers and another from native English speakers, made up a total of 940 participants in this study. The short forms were translated and adapted based on international guidelines. Reliability (internal and composite) and validity analyses (construct ESEM, concurrent, predictive and cross-cultural invariance through multi-group factorial models) were performed. Results For both the balanced scale and the PW one, modeling a method factor was not relevant. The reliability and validity indices of both forms were according to theory and prior studies’ findings: (a) personality factors were medium-high related to affective factors; (b) personality factors were less related to life satisfaction than affective factors; (c) life satisfaction was medium-high related to affective factors; (d) neuroticism appeared mainly related to all criteria variables; and (e) an acceptable level of invariance was achieved with regard to the English version. Discussion This study contributes to research on personality assessment by providing the first evidence regarding the psychometric properties of a PW short measure. These results suggest that PW short scales of personality used after data screening techniques may be appropriate for future studies (e.g., cross-cultural, content validity).